2020
DOI: 10.3390/ijms21249688
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy by Assisted Reproductive Technology Is Associated with Shorter Telomere Length in Neonates

Abstract: Telomere length (TL) influences the development of lifestyle-related diseases, and neonatal TL may influence their prevalence. Various factors have been reported to affect neonatal TL. Although the fetus is exposed to multiple conditions in utero, the main factors affecting the shortening of neonatal TL are still not known. In this study, we sought to identify factors that influence fetal TL. A total of 578 mother-newborn pairs were included for TL analysis. TL was measured in genomic DNA extracted from cord b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Several authors suggested telomere shortening as a potential mechanistic mediator not just of ageing and age-related diseases, but also of fetal programming [40]. Certain circumstances, such as psychosocial stress of the mother during pregnancy [41], conception after assisted reproductive technology [42] or intrauterine stress exposure, are associated with the length of offspring telomeres [43]. If mothers have the metabolic syndrome during pregnancy, it is associated with 14% shorter child telomeres compared with control children [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors suggested telomere shortening as a potential mechanistic mediator not just of ageing and age-related diseases, but also of fetal programming [40]. Certain circumstances, such as psychosocial stress of the mother during pregnancy [41], conception after assisted reproductive technology [42] or intrauterine stress exposure, are associated with the length of offspring telomeres [43]. If mothers have the metabolic syndrome during pregnancy, it is associated with 14% shorter child telomeres compared with control children [44].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the telomeric repeat-containing RNAs, known as TERRA, have been positively associated with embryo quality in in vitro fertilization/intracytoplasmatic sperm injection-embryo transfer (IVF/ICSI-ET) treatments [40]. Moreover, pregnancy success rates in the context of ART have been associated with shorter telomere length in newborns [41]. In that study, a number of factors have been investigated, including BMI, smoking status, alcohol and stress.…”
Section: The Role Of Telomeresmentioning
confidence: 99%
“…Genetic and environmental factors regulate telomere length throughout the lifespan of each person, starting from in utero conditions [ 15 17 ]. Tracking telomere length from birth to adulthood, it was recently shown that the newborn telomere predicts later life telomere length [ 18 ], pointing to the importance of determining the initial state of newborn telomere and its significance for later life [ 19 ]. Maternal exposures in pregnancy are critical predictors of telomere length in offspring as a long-term trajectory determining the susceptibility of the individual to chronic diseases [ 20 ].…”
Section: Introductionmentioning
confidence: 99%